Police performance and violent crime in Rio de Janeiro between 2007 and 2017 - Daniel Ganem Misse (Oñati International Institute for the Sociology of Law, 2021)
Performance-related pay policies applied to the Police have been implemented in Brazil and Latin America since the 2000s in an attempt to reduce the main violent crime indicators. The Integrated Targets System (Sistema Integrado de Metas - SIM), the Pacifying Police Units (Unidades de Polícia Pacificadora - UPP) and the Additional Service Regime (Regime Adicional de Serviço - RAS), initiated in the state of Rio de Janeiro in 2009, sought to reduce “strategic state crime indicators” whose results are monitored by the civil police report data. In order to understand how these policies have been implemented in the state of Rio de Janeiro between 2007 and 2017, the study adopts a quantitative approach upon criminal analysis and a qualitative one based on interviews and field observation at civil police stations and military police battalions.